Using production data for improved planning and control - Montes, Clara Diez (My University, 2011)
With the purpose of coping with the global competitiveness between lead companies there is a need for systematic methods to provide shorter production time and higher quality of the resulting system. Currently, there is a tendency to focus on the solution instead of looking for the requirements and the production management don´t realize the severe consequences it has. According to the PPA studies of Swedish manufacturing companies, and some other studies, there is a significant gap between operation times in reality and in the planning systems. In order to solve this, it is installed a new level in the structure of MPCS (Manufacturing Planning and Control Systems) between the ERP/APS system and the shop floor level, called MES (Manufacturing Execution System). Through that, it is provided real-time information to the managers that help them to take decisions based on facts. The objective of the study is to analyze the present software existing in the MES level in the company Good Solutions and the corresponding model of disturbances and production times in order to improve the planning and control. That is developed with real production data and it is checked what can be modified and improved on it. A model for production disturbances is given as well as some proposals with the intention of automating the decision process.
Keywords: Produktion; Produktionsteknik; Production; Manufacturing engineering